Advancing Keranggan Ecotourism Village with Human Resource Development and Business Development - Lia Siti Julaeha; Abdul Haris Muchtar; Ahmad Mauilidizen; Muhammad Rafi Thoriq; Aisyah Aulia Sugiarto; Ditha Anastasya Nurmahdina; Khoirunnisa Mufidah; Mendy Adhadisha Rahmat; Muhammad Salman Alfarizi Ashfaq; Muhammad Tegar Tawakkal; Nabila Khairani (SocietalServe: Journal of Community Engagement and Services, 2024)
The village is envisioned as a community-driven tourist destination, rooted in the cultural heritage and wisdom of its inhabitants, with the potential to serve as an engine for sustainable economic growth. Presently, the government is formulating a priority program aimed at instilling the principles of sustainable development within the tourism sector, with a specific emphasis on rural areas. These tourist villages are designed to serve as direct platforms for fostering community awareness about the tourism potential inherent in their surroundings, while also embodying the principles of Sapta Pesona within the local environment at tourist destinations. Moreover, they represent crucial partners for local governments, collaborating to realize and enhance tourism opportunities within their respective regions. Geographically, the Keranggan Ecotourism Village benefits from its proximity to the Cisadane river, located not far from the bustling city center of BSD. Blessed with natural beauty and conditions, alongside the livelihoods of numerous residents engaged in micro, small, and medium enterprises (MSMEs), particularly in producing a variety of chips, the village has become a hub of economic activity. This has led to the emergence of a multitude of MSME actors within sectors such as recreation, food, and homestay accommodations. Collaborative management initiatives, in tandem with several universities, have the potential to drive regional economic growth, while simultaneously preserving the environment and fostering prosperity among the local populace. Spanning across 20 hectares of land, the village is thoughtfully divided into various zones, each catering to different aspects of tourism, including culinary experiences, recreational activities, educational tours, and sports recreation facilities.